PERANCANGAN SPK TENTANG KETERAMPILAN MAHASISWA DENGAN METODE SAW - Niko Akbar (LPPM Universitas Abdurrab, 2023)
In college, there are hundreds of students, including in the classroom. Nowadays, students are equipped with technological assistance and work in instant ways so they don't consider aspects of basic abilities so they take actions that shouldn't be done, such as looking for answers with other friends. So they don't make answers based on their self-confidence and ability to solve their problems. Each student has their quality based on confidence in their abilities and skills. So to assess and determine some students who have confidence in the abilities needed research to produce alternatives to students who have the highest scores and choose the top of the assessment. This study aims to design a Decision Support System (DSS) using data in the form of students who are selected using the SAW calculation method. The results of the research help lecturers determine which students are the best in their abilities and have the skills for their beliefs.